Needs Analysis of Edupreneurship Learning in the English Language Education Study Program - Shilfani Shilfani; Mey Enggane Limbongan (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
Edupreneurship is a science that seeks to integrate entrepreneurship ideas, concepts, and attitudes into the world of education. Needs analysis is the first step in determining the problem overview, correcting, and finding problem solving to design the program from the next course. The goal of this research is to determine the needs of students in the Edupreneurship Course of the English Study Program, FKIP, UKI Toraja. The development method (Research and development/ R&D) was used in this study. Borg and Gall (1979:772) state that "R&D is a process used to develop and validate educational products." This research is based on efforts to produce and validate an educational product, according to this definition. In this study, researchers used a research instrument, namely a questionnaire, to collect data. That after data analysis, the researchers concluded that student needs in the English Study Program's Edupreneurship Course, FKIP, UKI Toraja, namely: The material for teaching edupreneurship is integrated with English language skills such as speaking, listening, reading, and writing. Respondents require group learning, training / workshops, learning in pairs, and learning alone (individually) when learning Edupreneurship. The respondents' high level of enthusiasm in responding to various topics such as the Presentation Method of independent/group assignments, independent/group tasks made in the form of videos and uploaded to social media, final tasks that produce a useful and selling value product, the need for business planning training, and Edupreneurship teaching materials on how to analyze new business opportunities.